Low temperature degradation resistant nanostructured yttria-stabilized zirconia for dental applications. Issue 7 (15th May 2016) - Tredici, Ilenia G.; Sebastiani, Marco; Massimi, Federico; Bemporad, Edoardo; Resmini, Alessandro; Merlati, Giuseppe; Anselmi-Tamburini, Umberto
Abstract: When used in prosthetic dentistry, zirconia encounters severe durability issues due to low temperature degradation: exposure to humidity results in a transition from tetragonal to monoclinic phase, associated to disruptive integrity loss. Recently it has been shown that size-induced stabilization helps maintaining zirconia in tetragonal form, when the grain size is reduced to the nano-range. Objective of this work is to demonstrate the applicability of High Pressure Field Assisted Sintering (HP-FAST) to the preparation of dense, nanostructured samples of tetragonal yttria stabilized zirconia, with yttria content between 0.5 and 3 mol% and showing resistance to low temperature degradation. The yttria stabilized zirconia nanopowders were prepared by a hydrothermal method. Sintering by HP-FAST was performed at 900 °C in 5 min, under a pressure of 620 MPa. Resistance to low temperature degradation was tested at 134 °C, under vapor pressure, for up to 40 h. Both pristine and aged samples were characterized by X-ray diffraction, high-resolution scanning electron microscopy and nanoindentation tests in continuous stiffness measurement mode. The sintered samples presented a grain size between 20 and 30 nm and low or null monoclinic content. Both parameters resulted unaffected by ageing. The best results in terms of phase composition and mechanical properties have been obtained with the material containing 1.5 mol% of yttria. These results induce to reconsider the use of yttria stabilized zirconia as material for dental prosthetic systems requiring long-term durability. Graphical abstract: